Effects of STEAMification Model in Flipped Classroom Learning Environment on Creative Thinking and Creative Innovation - Naphong Wannapiroon; Sirirat Petsangsri (My University, 2020)
This paper is a report on the findings from the research and development of STEAMification model in flipped classroom learning environment to enhance creative thinking and creative innovation. The purposes of this study are: 1) to develop the model; 2) to study the developed model. Results exhibited that: 1) the model consists of 6 components, 2) the students who had studied through STEAMification had higher creativity (Mean = 14.53, S.D. = 0.94) than the students who studied through normal model (Mean = 12.90, S.D. = 1.91), 3) the students who had studied through model had higher quality of creative innovation (Mean = 14.86, S.D. = 1.62) than the students who studied through normal model (Mean = 12.90, S.D. = 1.91).
Keywords: Flipped learning; Education and Learning Interventions